2016
DOI: 10.1007/s10967-016-4820-7
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and photocatalytic reduction activity of uranium(VI) on zinc oxide/rectorite composite enhanced with methanol as sacrificial organics

Abstract: In this work, zinc oxide/rectorite composites were synthesized by a sol-gel method. The methanol as sacrificial organics could be enhance the adsorption capability and photocatalytic reduction activity of U(VI) onto the zinc oxide/rectorite composites. In addition, the composite still showed the high photoreduction activity after four reaction cycles under visible light irradiation. On the basis of the experimental results and photoluminescence, the enhanced photoreduction activity could be attributed to charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In addition, the efficiency of five cycles is greater than 90%. Guo et al [ 92 ] synthesized zinc oxide/retorite composite material by sol–gel method. Using methanol as a sacrificial organic matter improves the adsorption capacity and photocatalytic reduction activity of U(VI) on zinc oxide/retorite composites.…”
Section: Treatment Technologies For Radioactive Wastewatermentioning
confidence: 99%
“…In addition, the efficiency of five cycles is greater than 90%. Guo et al [ 92 ] synthesized zinc oxide/retorite composite material by sol–gel method. Using methanol as a sacrificial organic matter improves the adsorption capacity and photocatalytic reduction activity of U(VI) on zinc oxide/retorite composites.…”
Section: Treatment Technologies For Radioactive Wastewatermentioning
confidence: 99%
“…Due to the complexity and diversity of natural water environments, the photocatalysts used for U extraction must have a relatively wide selectivity for different U(VI) species to improve uranium extraction efficiency. Herein, we list the studies on photocatalytic uranium extraction in recent years in Table 1 [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ].…”
Section: Mechanism Of Photocatalytic Uranium Reduction and Identifica...mentioning
confidence: 99%
“…Similarly, it has also been proven preliminary research work that the application of the photocatalytic method showed a high enhance for U(VI) in the presence of other hole scavenger including ethanol, methanol, sodium citrate and formic acid. 33,34 To conrm the possibility, the kinetics of U(VI) reduction at the interface of a-Fe 2 O 3 /TiO 2 the lm electrodes/electrolyte were evaluated by electrochemical impedance spectroscopy (EIS). The measured EIS spectra are shown in the form of Nyquist plots in Fig.…”
Section: Organic Acid Mediated Photoelectrochemical Reduction Of U(vi)mentioning
confidence: 99%